Herpes Zoster and Tofacitinib Therapy in Patients With Rheumatoid Arthritis - Winthrop, Kevin L (Arthritis Rheumatol, 2014)
OBJECTIVE: Patients with rheumatoid arthritis (RA) are at increased risk for herpes zoster (HZ) (i.e., shingles). The aim of this study was to determine whether treatment with tofacitinib increases the risk of HZ in patients with RA. METHODS: HZ cases were identified as those reported by trial investigators from the databases of the phase II, phase III, and long-term extension (LTE) clinical trials in the Tofacitinib RA Development Program. Crude incidence rates (IRs) of HZ per 100 patient-years (with 95% confidence intervals [95% CIs]) were calculated by exposure group. Logistic regression analyses were performed to evaluate potential risk factors for HZ (e.g., age, prednisone use). RESULTS: Among 4,789 participants, 239 were identified as having tofacitinib-associated HZ during the phase II, phase III, and LTE trials, of whom 208 (87%) were female and whose median age was 57 years (range 21–75 years). One HZ case (0.4%) was multidermatomal; none of the cases involved visceral dissemination or death. Twenty-four patients with HZ (10%) permanently discontinued treatment with tofacitinib, and 16 (7%) were either hospitalized or received intravenous antiviral drugs. The crude HZ IR across the development program was 4.4 per 100 patient-years (95% CI 3.8–4.9), but the IR was substantially higher within Asia (7.7 per 100 patient-years, 95% CI 6.4–9.3). Older age was associated with HZ (odds ratio 1.9, 95% CI 1.5–2.6), and IRs for HZ were similar between patients receiving 5 mg tofacitinib twice daily (4.4 per 100 patient-years, 95% CI 3.2–6.0) and those receiving 10 mg twice daily (4.2 per 100 patient-years, 95% CI 3.1–5.8). In the phase III trials among placebo recipients, the incidence of HZ was 1.5 per 100 patient-years (95% CI 0.5–4.6). CONCLUSION: In the Tofacitinib RA Development Program, increased rates of HZ were observed in patients treated with tofacitinib compared with those receiving placebo, particularly among patients within Asia. Complicated HZ among tofacitinib-treated patients was rare.